The Application of the Merdeka Curriculum in the Context of Learning Recovery - Masmida Putri, Yelli; Hanani , Silfia; Sesmiarni, Zulfani (TOFEDU: The Future of Education Journal, 2023)
Indonesia has been experiencing a learning crisis for quite a long time. The Covid 19 pandemic period is a special condition that causes learning to lag behind (learning loss). Curriculum implementation by educational units can use a curriculum that is appropriate to the learning needs of students and must pay attention to the achievement of student competencies in the educational unit in the context of learning recovery. The Merdeka Curriculum is a curriculum with diverse intracurricular learning where the content will be more optimal so that students have sufficient time to deepen concepts and strengthen competencies. The research method used is a literature review from related journals. Results: The independent learning policy was implemented to accelerate the achievement of national education goals, namely improving the quality of Indonesia's human resources which have superiority and competitiveness compared to other countries. The quality of superior and competitive human resources is realized in students who have noble character and have a high level of reasoning, especially in literacy and numeracy.